FPGA BASED ENERGY EFFICIENT HOME APPLIANCE CONTROL WITH EMBEDDED IoT - Mohanabarathy, R.; P, Pradeep; Dharshini R, Priya; M, Usha (International Journal of Psychosocial Rehabilitation, 2020)
The Home Automation concept is a brand new approach of wireless controlling of the home appliances. The terms “Smart Home”, “Intelligent Home” is Associated with the type of system and has been used to introduce the concept of networking appliance and devices in the home. This represents the power efficiency by adapting security and energy efficiency which is done by using FPGA controller based on the core system. In this the hardware method is explained and the software design is adopted completely by the flow of embedded product. It can analyse the real time information from the sensors by the switch system behavior consequently. Some parameters from automating the home mainly for energy saving into a great market. Nowadays we can see a technology enabled in digital network rapidly.